The Push of Social Pain: Does Rejection’s Sting Motivate Subsequent Social Reconnection? - Chester, David S. (Cogn Affect Behav Neurosci, 2016)
Physical pain motivates the healing of somatic injuries. Yet it remains unknown whether social pain serves a similarly reparative function towards social injuries. Given the substantial overlap between physical and social pain, we predicted that social pain would mediate the effect of rejection on greater motivation for social reconnection and affiliative behavior towards rejecters. In Study 1, the effect of rejection on an increased need to belong was mediated by reports of more intense social pain. In Study 2, three neural signatures of social pain (i.e., activity in the dorsal anterior cingulate cortex, left and right anterior insula during social rejection), each predicted greater behavioral proximity to rejecters. Our findings reify the overlap between social and physical pain. Further, these results are some of the first to demonstrate the reparative nature of social pain and lend insight into how this process may be harnessed to promote post-rejection reconnection.